Employee reviews on company independent sites and its impact on organizational attractiveness: role of information realism, person – environment fit and source credibility framework - Kaur, Tavleen; Dubey, Ritesh (Business: Theory and Practice, 2014)
Extant literature on recruitment has focused on the traditional sources of recruitment like company brochures, career fairs, and impact of such sources on intent to join the organization, productivity and turnover intention. The influence of recruitment related information on pre hire outcomes is still scarce and inconclusive. With the advent of technology and access to Internet, company websites have become an important source of recruitment. Apart from company websites, job seekers are now using company independent websites, forums or online communities to gather a more truthful picture and information about the job and organizational attributes. Social media too has become increasingly important medium where the current employees’ share how it is to work with the organization However research on web based recruitment is limited to company websites. Despite the widespread growth and practical use of these new and innovative media very little is known about how these independent sites influence recruitment pre hire outcomes. In this direction the proposed study presents a conceptual framework about how job seekers perceive company independent websites as a tool for providing recruitment communication and their impact on organizational attractiveness using Information Realism, Person-Environment fit framework, Source Credibility framework.